FACTORS RELATED TO THE LEVEL OF ACADEMIC STRESS IN ADOLESCENTS IN GRADE 12 OF SMA ISLAM PUTRADARMA, BEKASI REGENCY 2022 - Rayhanissa Aulia Cahyantari; Puji Raharja Santosa; Kiki Deniati (Rena Cipta Mandiri, 2024)
Hypertension, a chronic condition characterized by elevated blood pressure, poses significant health risks, particularly in elderly populations. This study, conducted at the Suka Tenang Health Center in Bekasi Regency on June 22, 2022, aimed to examine the relationship between lifestyle and hypertension among individuals aged ≥65 years. Using a quantitative approach with a cross-sectional design, the study utilized purposive sampling to select 56 elderly respondents from the Suka Tenang Health Center area. Univariate analysis revealed that the majority of respondents (69.6%) fell within the age range of 65-70 years, with an equal distribution of gender among respondents. Regarding lifestyle, 41.1% exhibited similar patterns. Bivariate analysis indicated that 65% of respondents with healthy lifestyles had mild hypertension levels, while 50.0% of those with unhealthy lifestyles did not have severe hypertension. Statistical analysis using the chi-square test yielded a significant p-value (0.000) at a 95% confidence level, indicating a rejection of the null hypothesis (H0). Therefore, it can be inferred that there is indeed a relationship between lifestyle and hypertension among elderly individuals aged ≥65 years at the Suka Tenang Health Center in Bekasi Regency, 2022. In conclusion, this study underscores the importance of lifestyle factors in the management and prevention of hypertension among elderly populations. Addressing lifestyle habits could potentially mitigate the risk of hypertension and its associated complications in this demographic.